SERVING TO EXCEL BY EMPHASIZING THE MEDIATING ROLE OF EMPLOYEE LOYALTY IN THE INFLUENCE OF SERVANT LEADERSHIP ON SERVICE QUALITY - Raden Eros Rostini; Zulganef Zulganef (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to analyze the influence of servant leadership on service quality, with employee loyalty as a mediating variable, at Bank OCBC NISP in Bandung Regency and West Bandung Regency. The research method used is quantitative with an explanatory research approach. Data were collected through questionnaires from 60 frontline employees using a total sampling technique. The results of the path analysis showed that servant leadership significantly influenced employee loyalty (B = 0.862; sig. = 0.000) and service quality (B = 0.634; sig. = 0.000). Employee loyalty was also proven to significantly influence service quality (B = 0.414; sig. = 0.000) and acted as a partial mediator in the relationship between servant leadership and service quality, as evidenced by the Sobel test (t = 10.10; p = 0.000). These findings confirm that strengthening servant leadership values ​​is able to shape employee loyalty which has an impact on improving overall service quality. However, descriptive results indicate implementation gaps in suburban branches, particularly in terms of managerial engagement and consistency of work culture. Therefore, an inclusive and adaptive leadership strategy is needed to ensure equitable service quality across the branch network.